Methane prediction of two tree fruits by In vitro gas and gas chromatography - Ramirez Diaz, Roselia; Pinto-Ruiz, René; Miranda Romero , Luis Alberto; La O Arias, Manuel Alejandro; Hernandez Sanchez, David; Ray Arial, Deb (Ecosistemas y Recursos Agropecuarios, 2023)
The objective of the present work was evaluate predictive models for methane production fruits Leucaena collinsii and Guazuma ulmifolia measured through the in vitro gas production technique (TPG) and gas chromatography. The fruits were subjected to a chemical analysis, in vitro fermentation using the gas production technique GPT, and methane was measured using gas chromatography and the GPT. A correlation and regression analysis was conducted to determine the equations and the determination coefficients (R2) between CH4 using gas chromatography and CH4 estimation from the TPG. A positive trend was found between the estimation of methane by gas chromatography and by the TGP. It is concluded that the in vitro gas technique is promising for the determination of methane from Leucaena collinsii and Guazuma ulmifolia fruits compared to the conventional reference technique, gas chromatography.